Enhanced critical current density of Garnet Li7La3Zr2O12 solid electrolyte by incorporation of LiBr. (20th March 2022) - Ma, Xiaoning; Xu, Youlong
ABSTRACT: Cubic garnet Li7 La3 Zr2 O12 (LLZO) solid electrolytes have a strong potential to allow solid-state lithium-ion to become the next-generation energy storage systems and for addressing the safety issues. However, the applications of LLZO solid electrolytes are seriously limited by the relatively low critical current density of LLZO. In this study, we introduce lithium bromide (LiBr) with a low melting point as the sintering aid to prepare a high-performance garnet with high ionic conductivity, high relative density, and excellent critical current density. The prepared LLZO solid electrolyte with a LiBr concentration of 0.15 ( x LiBr–LLZO with x  = 0.15 mol) exhibited a high ionic conductivity of 7.62 × 10 −4 S cm −1 at 25 ℃ with an excellent relative density of 96.27%. The critical current density (CCD) of the symmetric Li | 0.15LiBr–LLZO | Li cell was 1.0 mA cm −2 at 25 ℃. Furthermore, this cell can stably operate for 1000 h under a current density of 0.3 mA cm −2 . In addition, quasi-solid-state batteries of Li | LiFePO4 with 0.15LiBr–LLZO electrolyte delivered excellent capacity retention (141.1 mAh g − 1 ; ∼89.7%) after 300 cycles, excellent rate performance, high coulombic efficiency and cycling stability. Furthermore, Li | LiNi0.8 Co0.1 Mn0.1 O2 with 0.15LiBr–LLZO electrolyte could run normally with high coulombic efficiency (>99%). These research results show that the solid-state batteries developed using 0.15LiBr–LLZO electrolyte are highly promising for the practical applications.